Paradox of peroxy defects and positive holes in rocks. Part I: Effect of temperature. (15th December 2015) - Freund, Friedemann T.; Freund, Minoru M.
Highlights: Paradoxically, rocks from reduced environments contain peroxy, hallmark of oxidizing conditions. Peroxy are introduced under non-equilibrium conditions, when diffusion has slowed to standstill. Redox conversion changing pairs of hydroxyls into molecular H2 plus peroxy can still take place. When the H2 molecules diffuse from the site, where they were "born", reaction becomes irreversible. Peroxy defects release highly mobile positive hole charge carriers. Abstract: Most non-seismic, non-geodesic pre-earthquake phenomena are believed to be controlled by the stress-activation of peroxy defects in rocks, which release highly mobile electric charges. Though ubiquitous in minerals of igneous and high-grade metamorphic rocks, peroxy defects have been widely overlooked in the past. The charge carriers of interest are positive holes, chemically equivalent to O − in a matrix of O 2−, physically defect electrons in the O 2− sublattice, highly mobile, able to propagate fast and far. O − are oxidized relative to O 2− . As such O − are not supposed to exist in minerals and rocks that come from deep within the Earth's crust, where the environments are overwhelmingly reduced. The presence of O − appears to contradict thermodynamics. However, there is no conflict. In order to understand how peroxy defects are introduced into common rock-forming minerals, over which temperature window they release positive holes, and how this may be related to pre-earthquake phenomena, we look at peroxy defects in a crystallographically and compositionally well characterized model system: single crystals of nominally high-purity MgO, grown from the melt under highly reducing conditions. During crystallization the MgO crystals incorporate OH − through dissolution of traces of H2 O in the MgO matrix, leading to a solid solution (ss) Mg1− δ (OH)2 δ O1−2 δ, where δ  ≪ 1. During cooling, the ss leaves thermodynamic equilibrium, turning into a metastable supersaturated solid solution (sss). Using infrared (IR) spectroscopy it is shown that, during further cooling, OH − pairs at Mg 2+ vacancy sites rearrange their electrons, undergoing a redox conversion, which leads to peroxy anions, O2 2−, plus molecular H2 . Being diffusively mobile, the H2 molecules can leave the Mg 2+ vacancy sites, leaving behind cation-deficient Mg1− δ O. During reheating, but in the sss range, the O2 2− break up, releasing positive hole charge carriers, which profoundly affect the electrical conductivity behavior. In igneous mafic and ultramafic rocks, similar changes in the electrical conductivity are observed in the temperature window, where peroxy defects of the type O3 Si-OO-SiO3 break up. They release positive holes, which control the electrical conductivity response. Deciphering these processes helps understanding the stress-activation of positive holes along the geotherm.